Climatic regulation of dormancy and emergence of diverse Malva parviflora populations from a Mediterranean-type environment - Michael, Pippa; Steadman, K.; Plummer, J. (CABI Publishing, 2006)
Malva parviflora L. (Malvaceae) is rapidly becoming a serious weed of Australian farming systems. An understanding of the variability of its seed behaviour is required to enable the development of integrated weed management strategies. Mature Malva parviflora seeds were collected from four diverse locations in the Mediterranean-type climatic agricultural region of Western Australia. All of the seeds exhibited physical dormancy at collection; manual scarification or a period of fluctuating summer temperatures (50/20oC and natural) were required to release dormancy. When scarified and germinated soon (1 month) after collection, the majority of seeds were able to germinate over a wide range of temperatures (5-37oC) and had no light requirement. Germination was slower in seeds stored for 2 months than seeds stored for 2 years suggesting the presence of shallow physiological dormancy. Seed populations from regions with similar annual rainfall exhibited similar dormancy release patterns; seeds from low rainfall areas (337 – 344 mm) were more responsive to fluctuating temperatures, releasing physical dormancy earlier than those from high rainfall areas (436 – 444 mm). After 36 months, maximum seedling emergence from soil in the field was 60% with buried seeds producing 13 – 34% greater emergence than seeds on the surface. Scanning electron microscopy of the seed coat revealed structural differences in the chalazal region of permeable and impermeable seeds indicating the importance of this region in physical dormancy breakdown of M. parviflora seeds. The influence of rainfall during plant growth in determining dormancy release, and hence germination and emergence timing, must be considered when developing management strategies for M. parviflora.